Lone McGantry: The Forever Mountain - Book 3 - Dundee, Wayne D. (Thorndike, Maine : Center Point Large Print, 2023)
"The dying request of an old friend sends former Indian scout Lone McGantry on a perilous journey from the barren Nebraska Sandhills to the ragged, snowy peaks of the Colorado Rockies. Danger dogs his trail right from the start, beginning with a pack of vengeful brothers out for his blood. Along the way, Lone crosses paths with a gang of ruthless robbers and also learns that a bounty placed on his head by a misguided cattle baron is responsible for hired guns swarming the territory in search of collecting the pay-out. The only bright spot in any of this is the companionship of an abandoned Oriental beauty with her own desperate need to reach the mountains. Lones grudging agreement to escort her adds complications, but it also adds a bittersweet hint of romance he didnt know he was missing."--
Keywords: Voyages and travels -- West (U.S.); Fiction; Revenge -- Fiction; Chinese -- United States; Fiction; Last words -- Fiction; Man-woman relationships -- Fiction; West (U.S.) -- Fiction; Western fiction; Large print books